Field evaluation of COVID-19 antigen tests versus RNA based detection: Potential lower sensitivity compensated by immediate results, technical simplicity, and low cost - Matsuda, Elaine Monteiro; Campos, Ivana Barros de; Oliveira, Isabela Penteriche de [UNESP]; Colpas, Daniela Rodrigues; Carmo, Andreia Moreira dos Santos; Brigido, Luis Fernando de Macedo (Wiley-Blackwell, 2021)
One year into the coronavirus disease 2019 (COVID-19) pandemic, diagnostic strategies, although central for contact tracing and other preventive measures, are still limited. To meet the global demand, lower cost and faster antigen tests for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) detection are a convenient alternative to the gold standard reverse transcription-polymerase chain reaction (RT-PCR) assay. We tested laboratory-based RT-PCR RNA detection and two rapid antigen detection (RAD) tests, based on the immunochromatography test for nucleocapsid protein of SARS-CoV-2 (COVID-19 Ag ECO Test, ECO Diagnostica, and Panbio COVID-19 Ag Rapid Test Abbott). Paired collection and testing were done in a small prospective open study in three clinical services in Sao Paulo, constituted of mostly symptomatic volunteers at collection (97%, 109/112) for a median of 4 days (interquartile range: 3-6), ranging from 1 to 30. Among the 108 paired RT-PCR/RAD tests, results were concordant in 96.4% (101/108). The test's performance was comparable, with an overall sensitivity of 87% and a specificity of 96%. These observations add to other data that suggest that antigen tests may provide reasonable sensitivity and specificity and deserve a role to improve testing strategies, especially in resource-limited settings.
Keywords: COVID‐ 19; diagnostic; gargle lavage; nasopharyngeal swab; rapid antigen detection; SARS‐ CoV‐ 2